A Strategic Set as an Essential Tool for the Development of Agricultural Enterprises - Yakubiv Valentyna M.; Boryshkevych Iryna I. (Problemi Ekonomiki, 2017)
The aim of the article is to define the essence of the term “strategic set” through studying the approaches of various scientists to this concept, generalizing the existing types of strategies and their reducing to the features of the agricultural sector, as well as highlighting the need to form a strategic set for the development of agricultural enterprises. In the process of writing the article the following methods of scientific knowledge were used: the methods of induction and deduction, the method of logical analysis — at substantiating the existing concepts of the strategic set and varieties of strategies; the method of theoretical modeling — to develop the concept of strategic set; the method of systematization — at conducting the comprehensive study of enterprise development strategies and their generalization. The existing approaches to the definition of the essence of the concept “strategic set” are analyzed. The strategic set is studied as an effective and integral tool for ensuring the competitiveness of an agricultural enterprise. Proceeding from the current tendencies in the agrarian market, the interpretation of the term “strategic set” as well as two new types of strategy is proposed. It is established that a correctly developed set of strategies forms the basis of strategic planning and is the key to the success of an agricultural enterprise. The scientific novelty of the study is in the generalization and deepening of the theoretical provisions concerning the strategic set, improvement of the conceptual-categorical apparatus and complementation of the existing types of strategies with new ones according to the current state of the agricultural sector.